PROFESIONALISME PADA KUALITAS AUDIT DENGAN GENDER SEBAGAI MODERASI - Silmi, Silmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to uncover the moderating effect of gender on the influence of professionalism on audit quality. With descriptive and associative research, the sample consists of State Civil Apparatus (ASN) who work as internal auditors at the Bukittinggi City Inspectorate Office. In this research, the random sampling method was used to select 30 respondents as samples. Data was collected through a questionnaire with closed questions and secondary data from documentation. The data analysis technique applied is quantitative analysis using the Structural Equation Model (SEM), which allows testing measurement and structural models simultaneously. The research results show that professionalism has a positive influence on audit quality. Furthermore, it was revealed that male gender has a greater moderating effect on the relationship between professionalism and audit quality when compared to female gender.Keywords: Professionalism, Audit Quality, Gender, Bukittinggi City Inspectorate